Atractylenolide-I Sensitizes Triple-Negative Breast Cancer Cells to Paclitaxel by Blocking CTGF Expression and Fibroblast Activation - Wang, Meng; Li, Xue-Zhen; Zhang, Ming-Xing; Ye, Qian-Yu; Chen, Ying-Xia; Chang, Xu (Frontiers in Oncology, 2021)
This investigation was conducted to elucidate whether atractylenolide-I (ATL-1), which is the main component of Atractylodes macrocephala Koidz, can sensitize triple-negative breast cancer (TNBC) cells to paclitaxel and investigate the possible mechanism involved. We discovered that ATL-1 could inhibit tumor cell migration and increase the sensitivity of tumor cells to paclitaxel. ATL-1 downregulated the expression and secretion of CTGF in TNBC cells. Apart from inhibiting TNBC cell migration via CTGF, ATL-1 downregulated the expression of CTGF in fibroblasts and decreased the ability of breast cancer cells to transform fibroblasts into cancer-associated fibroblasts (CAFs), which in turn increased the sensitivity of TNBC cells to paclitaxel. In a mouse model, we found that ATL-1 treatments could enhance the chemotherapeutic effect of paclitaxel on tumors and reduce tumor metastasis to the lungs and liver. Primary cultured fibroblasts derived from inoculated tumors in mice treated with ATL-1 combined with paclitaxel expressed relatively low levels of CAF markers. Collectively, our data indicate that ATL-1 can sensitize TNBC cells to paclitaxel by blocking CTGF expression and fibroblast activation and could be helpful in future research to determine the value of ATL-1 in the clinical setting.